Pembelajaran Menulis Eksposisi dengan Menggunakan Model Pembelajaran Problem Based Instruction - Maulana, Nanang (Jurnal Artikula, 2022)
The research, entitled "Learning to Write Exposition Using Problem Based Instruction Learning Model, aims to find or find out the results of using Problem Based Instruction learning methods in learning to write exposition. In this study, the author uses a quantitative approach, namely quasi-experimental research with research techniques used include literature review, trial, analysis technique, test or assessment technique. From the results of research conducted that Problem Based Instruction is appropriate to use in learning to write an exposition. This is evident from the results of statistical calculations and the results of the calculation of the significance level of the two mean differences between the pretest and posttest values, it is known that tcount 12.30 > ttable 2.04 at a significance level of 0.05 with 24 degrees of freedom. That is, learning to write exposition using the Problem Based method. Instructions are good. Thus, the author concludes that the Problem Based Instruction method is appropriate to use in learning to write exposition in class X high school students.